Labour History and the Case against Colonialism. (28th March 2019) - Brandon, Pepijn; Sarkar, Aditya
Abstract: The controversy around Bruce Gilley's article "The Case for Colonialism" has drawn global attention to a stream of revisionist claims and visions on the history of colonialism that has emerged in academia and in the media in recent years. Authors such as Nigel Biggar in the UK, Niall Ferguson in the USA, and Pieter Emmer in the Netherlands, have all published similarly revisionist claims about colonialism, arguing that postcolonial guilt and political correctness blind the majority of their colleagues to the positive side of the colonial project. Their argument chimes with wider societal trends, transforming the revisionist defenders of empire into heroes of a reinvigorated nationalist right within and beyond academia. The public influence attained by these approaches to colonialism requires historians to expose the deep methodological flaws, misreading of historical facts, and misrepresentations of prior scholarship that characterize the writings of this emerging revisionist trend. It is for this reason that the Editorial Committee of the International Review of Social History ( IRSH ) has decided to devote its first ever Virtual Special Issue to labour history's case against colonialism. This article, also an introduction to the Virtual Special Issue, sifts through the logical implications of the claims made by Gilley and like-minded scholars, providing both a contextualization and a rebuttal of their arguments. After assessing the long absence of colonial labour relations from the field of interest of labour historians and the pages of the IRSH itself, this article shows the centrality of a critique of colonialism to labour history's global turn in the 1990s. Using a selection of articles on colonial labour history from the IRSH 's own archive, the article not only reconstructs "labour history's case against colonialism", but also shows why labour history's critical insights into the nature of colonialism should be deepened and extended, not discarded. Abstract : La controverse autour de l'article de Bruce Gilley, "The Case for Colonialism" a attiré l'attention mondiale vers un courant de revendications et de vues révisionnistes sur l'histoire du colonialisme, né ces dernières années dans le monde universitaire et les médias. Des auteurs tels que Niger Biggar au R.U., Niall Ferguson aux E.U. et Piet Emmer aux Pays-Bas ont tous publié des revendications semblablement révisionnistes sur le colonialisme, soutenant que la culpabilité postcoloniale et le "politiquement correct" aveuglent la majorité de leurs collègues quant au côté positif du projet colonial. Leur argument fait écho à des tendances sociétales plus larges, transformant les défenseurs révisionnistes de l'empire en héros d'un droit nationaliste revigoré dans le monde universitaire et au-delà de ce dernier. L'influence publique que ces approches du colonialisme ont atteinte contraint les historiens à dénoncer les graves erreurs méthodologiques, la mauvaise lecture de faits historiques et les fausses représentations de connaissances antérieures qui caractérisent les écrits de cette tendance révisionniste émergente. C'est pour cette raison que le Comité éditorial de l' International Review of Social History ( IRSH ) a décidé de consacrer son tout premier Virtual Special Issue aux accusations de l'histoire du travail contre le colonialisme. Cet article, qui est également une introduction au Virtual Special Issue, examine minutieusement les implications logiques des revendications de Gilley et des érudits du même courant de pensées, en contextualisant et réfutant leurs arguments. Après avoir évalué la longue absence de la relation de travail colonial dans le champ d'intérêt des historiens du travail, et des pages de l' IRSH elle-même, cet article montre qu'une critique du colonialisme est au centre du tournant mondial de l'histoire du travail dans les années 1990. En utilisant un choix d'articles sur l'histoire du travail colonial provenant des propres archives de l' IRSH, l'article construit non seulement "l'histoire du travail contre le colonialisme", mais montre aussi pourquoi il conviendrait d'approfondir et d'élargir les aperçus critiques de l'histoire du travail concernant la nature du colonialisme. Traduction: Christine Plard Abstract : Die Kontroverse um Bruce Gilleys Aufsatz »The Case for Colonialism« (»Argumente zugunsten des Kolonialismus«) hat weltweit Aufmerksamkeit auf die stete Folge revisionistischer Aussagen und Sichtweisen auf die Kolonialgeschichte gezogen, die in den vergangenen Jahren sowohl im akademischen Bereich als auch in den Medien zu verzeichnen gewesen ist. Autoren wie Nigel Biggar aus Großbritannien, Niall Ferguson aus den USA und Piet Emmer aus den Niederlanden sind sämtlich mit vergleichbar revisionistischen Aussagen über den Kolonialismus an die Öffentlichkeit gegangen und haben dahingehend argumentiert, postkoloniale Schuldgefühle und political correctness würden der Mehrheit ihrer Kollegen die Sicht auf die positiven Aspekte des kolonialen Projekts verstellen. Diese These stößt aufgrund allgemeinerer gesellschaftlicher Entwicklungen auf Anklang, sodass die revisionistischen Fürsprecher imperialer Politik zu den Helden einer innerhalb wie außerhalb des akademischen Bereichs neu erstarkenden nationalistischen Rechten werden. Der öffentliche Einfluss, den diese Herangehensweisen an den Kolonialismus mittlerweile entfalten, verlangt von Historikern, dass sie die gravierenden methodologischen Fehler, die Fehldeutung historischer Tatsachen und die verzerrte Darstellung früherer Forschungsarbeiten aufdecken, durch die sich die Schriften dieser erstarkenden revisionistischen Tendenz auszeichnen. Aus diesem Grund hat sich der Redaktionsausschuss der International Review of Social History ( IRSH ) entschlossen, erstmalig eine virtuelle Sonderausgabe herauszugegeben, die arbeitshistorischen Argumenten gegen den Kolonialismus gewidmet ist. Der Beitrag, der zugleich die Einleitung zur virtuellen Sonderausgabe ist, erkundet die logischen Implikationen der von Gilley und vergleichbar gesinnten Forschern getätigten Behauptungen und arbeitet zugleich auf eine Kontextualisierung sowie auf eine Widerlegung ihrer Argumente hin. Nach einer Auseinandersetzung mit dem langjährigen arbeitshistorischen Desinteresse an kolonialen Arbeitsverhältnissen, wie es sich auch in der Themenwahl der Zeitschrift IRSH niedergeschlagen hat, arbeitet der Beitrag die zentrale Rolle heraus, die die Kritik am Kolonialismus beim global turn der Arbeitsgeschichte in den 1990er Jahren gespielt hat. Unter Rückgriff auf ausgewählte Untersuchungen zur kolonialen Arbeitsgeschichte aus dem IRSH -Archiv formuliert der Beitrag nicht nur »Argumente gegen den Kolonialismus«, sondern zeigt darüber hinaus auch die Gründe auf, aus denen es die kritischen Einsichten der Arbeitsgeschichte in das Wesen des Kolonialismus zu vertiefen und auszuweiten gilt. Übersetzung: Max Henninger Abstract : La controversia suscitada por el artículo de Bruce Gilley "The Case for Colonialism" ha generado una atención generalizada hacia una corriente de planteamientos revisionistas y de visiones de la historia del colonialismo que emergió en el ámbito académico y en los medios de comunicación a lo largo de los últimos años. Autores como Nigel Biggar en el Reino Unido, Niall Ferguson en los Estados Unidos y Piet Emmer en los Países Bajos han publicado tetos revisionistas sobre la cuestión del colonialismo desde perspectivas muy semejantes sosteniendo que la culpa postcolonial y la corrección política han hecho que la mayoría de sus colegas no vean el lado positivo del proyecto colonial. Sus argumentos enlazan con tendencias sociales muchos más amplias transformando a estos revisionistas defensores del imperio en heroes de una derecha nacionalista revigorizada dentro y fuera del mundo académico. La influencia pública alcanzada por estas perspectivas sobre el colonialismo obliga a quienes nos dedicamos a la historia a poner al descubierto los graves defectos metodológicos, la interpretación errónea de hechos históricos y la tergiversación de propuestas previas que caracterizan los escritos de esta corriente revisionista emergente. Precisamente por esta razón el Comité Editorial de la International Review of Social History ( IRSH ) ha decidido dedicar su primer número especial virtual a la cuestión del proceso de la historia del trabajo contra el conlonialismo. En este artículo, que sirve de introducción a este número virtual especial, hace un repaso de las implicaciones lógicas de las propuestas realizadas por Gilley y otros académicos que secundan esta corriente, elaborando tanto una contetualización de estas propuestas como una refutación de los argumentos que presentan. Después de realizar un análisis de la larga ausencia de la cuestión de las relaciones laborales coloniales como ámbito de interés de los historiadores/as del trabajo, incluso en las propias páginas de la IRSH, en este artículo se demuestra la centralidad de una crítica al colonialismo en el giro global que se tuvo lugar en la historia del trabajo en la década de 1990. Haciendo uso de una selección de textos sobre la historia del trabajo colonial existentes en el archivo de la IRSH no sólo se construye un proceso de la historia del trabajo contra el colonialismo sino que también demuestra porqué debe de seguir profundizándose y extenderse la perspectiva crítica de la historia del trabajo sobre la naturaleza del colonialismo. Traducción: Vicent Sanz Rozalén